Farmer-led approach supports socially inclusive innovations in Kenya's dairy sector - Omayio, Esther; DuttaGupta, Tanaya; Bullock, Renee; Kiptoo Emmaculate; Maiyo, Nathan; Habermann, Birgit; Crane, Todd A. (International Livestock Research Institute, 2024)
In rural Kenya, adaptation practices in dairy shape and are shaped by gender relations in households. Men own the cows and control income, while women provide much of the labour. Working with 'adaptation pioneer households', the Pioneer Positive Deviance (P-PD) approach supports farmer-led innovation that is sustainable and socially inclusive. Esther Omaiyo, a livestock extension officer in Nandi County with over 15 years of experience, shares insights into her work and how the P-PD approach to scale with households is different and impactful.